The Impact of the Campus Teaching Program on Students' Literacy and Numeracy Skills at SMPN 9 Mataram - Susanti Susanti; Lalu Sumardi; Edy Kurniwansyah; Muh. Zubair (STKIP Taman Siswa Bima, 2025)
The purpose of this study was to determine the elements that promote and inhibit student growth and investigate the impact of the school's teaching program on the literacy and numeracy skills of SMPN 9 Mataram students. A case study methodology in conjunction with a qualitative approach was employed in order to completely comprehend the events that were witnessed. Interviews and documentation were used to gather data. Data reduction, data display, and conclusion drawing using the Miles and Huberman model were the steps that comprised data analysis. The researcher used triangulation techniques, including technical triangulation, source triangulation, and time triangulation, to ensure the veracity of the data. The campus teaching model has greatly enhanced students' literacy and numeracy abilities. To have a long-lasting and sustainable beneficial influence on raising the standard of instruction in primary and secondary education units, this program needs constant work and refinement. There are supporting and inhibiting factors in implementing the campus teaching program. This program requires support from the school. Support from the school refers to efforts to provide direction, facility assistance and other full support for the implementation of existing programs. Behind every successful program implementation, challenges are inevitably encountered—this also applies to the campus teaching program. Various obstacles can influence the effectiveness of the program in enhancing literacy and numeracy skills. These include limited time, low student motivation, and insufficient support from parents.